Thidiazuron-Induced Somatic Embryogenesis in Cymbidium bicolor Orchid In Vitro - Istiqomah, Azura Muzdalifah; Setiari, Nintya; Nurchayati, Yulita (PLANTA TROPIKA, 2025)
Cymbidium bicolor is a highly hunted and traded orchid, leading to a decline in its wild population. Orchid conservation can be achieved through tissue culture, particularly via somatic embryogenesis. Thidiazuron (TDZ) is a growth regulator used to induce somatic embryogenesis. This study aimed to determine the optimal TDZ concentration for somatic embryo formation. Stem explants of C. bicolor were cultured on Murashige Skoog (MS) medium with TDZ concentrations of 0, 1, 2, and 3 ppm. Observations were conducted weekly for two months using a stereo microscope and OptiLab. Variables observed included the percentage of green explants, somatic embryo formation time, the number of explants forming somatic embryos, and the number and morphology of somatic embryos. The study was arranged in a Completely Randomized Design (CRD) with 14 replications. Results showed that TDZ addition influenced somatic embryo formation and maintained the green color of explants. Media with TDZ promoted faster growth and larger embryo size compared to media without TDZ. The optimal concentration was 1 ppm TDZ, which produced the highest number of embryos (172) and the fastest formation time compared to other concentrations (TDZ 0: 27, TDZ 2 ppm: 60, TDZ 3 ppm: 39).